2009
DOI: 10.3852/07-164
|View full text |Cite
|
Sign up to set email alerts
|

Morphological measurements and ITS sequences show that the new alder rust in Europe is conspecific withMelampsoridium hiratsukanumin eastern Asia

Abstract: Three species of Melampsoridium have been reported to infect hosts in genus Alnus. An epidemic of foliar rust affecting A. glutinosa and A. incana began in Europe in the mid-1990s, and the associated pathogen was identified as Melampsoridium hiratsukanum based on morphology. In this investigation we analyzed the morphology and genetic variation of alder rusts from Europe and Japan and the host specificity of the European epidemic rust. Our results showed that two rusts occur on the leaves of alders native to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…The agent was identified as Melampsoridium hiratsukanum S. Ito ex Hirats. based on morphological characterization and later was confirmed by molecular data (Hantula et al 2009). …”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The agent was identified as Melampsoridium hiratsukanum S. Ito ex Hirats. based on morphological characterization and later was confirmed by molecular data (Hantula et al 2009). …”
Section: Introductionmentioning
confidence: 82%
“…in Japan (Hiratsuka 1927) and was reported as native species in Far East Asia (Kuprevich, Tranzschel 1957;Hiratsuka et al 1992;Gjaerum 1996;Chen 2002;Cho, Shin 2004;Kobayashi 2007 Kaneko, Hiratsuka 1981;Roll-Hansen, Roll-Hansen 1981). The detailed comparison of urediospore morphology and r-DNR sequence analysis of the ITS region showed that European population of M. hiratsukanum is conspecific with population of this fungus from Eastern Asia and that both populations belong to a single palearctic population (Hantula et al 2009). In Europe this aggressive rust commonly cause considerable damage to foliage of grey alder, but may also infect more resistant black alder and cause serious problems in forest stands mixed with larch (Kurkela et al 1999;Hantula et al 2009).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…(Pucciniastraceae) poses a serious menace to natural stands and plantations of alder in several countries of central and eastern Europe. A native of eastern Asia (Hiratsuka 1927), this invasive parasite was first reported in the Baltics in the mid-1990s, where it arrived presumably through the trade in nursery plants (Põldmaa 1997;Hantula & Scholler 2006;Hantula et al 2009). In the last twenty years it has spread epidemically across a number of countries along a northesouth axis roughly running from latitude 60 N (Finland) to latitude 38 N (Turkey), parasitising a number of the alder species (Alnus incana Moench., Alnus cordata Loisel, Alnus glutinosa Gaertn., Alnus orientalis Decne., and Alnus viridis D.C.) it encountered in its fairly rapid descent southwards (Kreisel & Scholler 1994;Pią tek et al 2001;Szabo 2002;Rigler-Hager et al 2003;Sert & S€ umbul 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kleb., and Melampsoridium carpini (Nees) Dietel also occur on representatives of the family Betulaceae (members of the genera Alnus, Betula, Carpinus, Corylus, and Ostrya) in the northern hemisphere (Wilson & Henderson 1966). Likewise M. hiratsukanum, M. alni, and M. betulinum also infect the genus Alnus (G€ aumann 1959;Roll-Hansen & Roll-Hansen 1981;Hantula et al 2009) and these fungi have long been recorded in the Italian Peninsula (Trotter 1914;Saccardo 1988Saccardo , 1905.…”
Section: Introductionmentioning
confidence: 99%